Characterization of integrative and conjugative elements carrying antibiotic resistance genes of Streptococcus suis isolated in China - Wang, Jianping; Qi, Kexin; Bai, Xuemei; Wu, Zongfu; Kang, Weiming; Liang, Pujun; Zheng, Han; Xu, Jianguo (Frontiers in Microbiology, 2022)
Streptococcus suis, an emerging zoonotic pathogen, is important reservoirs of antibiotic resistance genes that play critical roles in the horizontal transfer of corresponding resistances. In the present study, 656 antibiotic resistance (AR) genes were detected in 154 of 155 genomes of S. suis strains isolated from the nasopharynx of slaughtered pigs and the lungs of diseased pigs in China. The AR genes were clustered into 11 categories, consisting of tetracycline, macrolides, lincosamide, streptogramin, aminoglycoside, trimethoprim, amphenicols, nucleoside, quinupristin/dalfopristin, glycopeptide, and oxazolidinones resistance genes. In order to investigate the transmission patterns of the AR genes, AR genes-associated the mobile genetic elements (MGEs) were extracted and investigated. Twenty ICEs, one defective ICE, one tandem ICE, and ten prophages were found, which mainly carried tetracycline, macrolides/lincosamides/streptogramin (MLS), and aminoglycosides resistance genes. Three types of DNA cargo with AR genes were integrated into specific sites of ICEs: integrative mobilizable elements (IMEs), cis-IMEs (CIMEs), and transposon Tn916. Obvious differences in AR gene categories were found among the three cargo types. IMEs mainly harbored tetracycline and MLS resistance genes. CIMEs mainly carried aminoglycoside resistance genes, while transposon Tn916 carried only the tet (M) gene. Nearly all AR genes in ICEs were carried by IMEs and CIMEs. IMEs were prevalent and were also detected in additional 29 S. suis genomes. The horizontal transfer of IMEs and CIMEs may play critical role in ICE evolution and AR gene transmission in the S. suis population. Our findings provide novel insights into the transmission patterns of AR genes and the evolutionary mechanisms of ICEs in S. suis.